Uso de Biosolidos en Produccion de Hortalizas - Mónica Ozores-Hampton; Joel Mendez (EDIS)
HS1183, an 11-page Spanish-language fact sheet by Mónica Ozores-Hampton and Joel Mendez, describes the use of biosolids in vegetable production — processes used to reduce pathogens, plant nutrients, regulations concerning the use of biosolids, how much to use, and effective application. Includes references. Published by the UF Department of Horticultural Sciences, August 2010.